The Amazon‐Orinoco Barrier as a driver of reef‐fish speciation in the Western Atlantic through time - Gabriel S. Araujo; Luiz A. Rocha; Naomi S. Lastrucci; Osmar J. Luiz; Fabio Di Dario; Sergio R. Floeter (Journal of Biogeography, 2022)
Aim The Amazon‐Orinoco plume is the major biogeographical barrier between the Great Caribbean and the Brazilian Province. No study has so far addressed the influence of this barrier in a broad chrono‐phylogenetic context. Here, we evaluate the effects of the Amazon‐Orinoco plume barrier on the patterns of diversification of Western Atlantic reef fishes through time. Location Tropical Western Atlantic. Taxon Reef Fishes (Percomorpha). Methods We compiled DNA sequence data of 21 molecular markers from sister species/population pairs across 33 reef‐fish families in the Greater Caribbean biogeographical region and the Brazilian Province. The data included estimated divergence times between sister‐pairs based on previously published phylogenies and 94 newly proposed time‐trees. Divergence dates were compared with variations in the sedimentation discharge rate of the Amazon River and sea‐level fluctuations. To address the hypothesis that fishes with different adult sizes are affected differently by the Amazon‐Orinoco plume, we used a phylogenetic least squares regression to test the relationship between maximum total body length and divergence times between the Caribbean and Brazilian sister‐pairs. Results We identified an increase in the rates of lineage diversification between sister‐pairs of the Greater Caribbean and Brazilian Province reef fishes in the past 2.4 million years, in accordance with the period of higher sedimentation rates of the Amazon River and the more frequent sea‐level fluctuations in the Pleistocene. A strong relationship between total body length and effectiveness of the barrier through time was confirmed, with smaller species typically diverging earlier in periods when sedimentation rates of the Amazon River were significantly lower. Conclusions The strong biogeographical signal detected in this study across different lineages of reef fishes clearly indicates that the Amazon‐Orinoco plume played a significant role in the diversification of the Atlantic reef‐fish fauna. The temporal pattern of diversifications indicates a correlation between the permeability of the plume, sea‐level fluctuations, variability in the volume of the discharge and fish body size, with the barrier's influence being weaker on larger fishes.